Learning disabilities : theories, diagnosis, and teaching strategies - Lerner, Janet W. (Boston, Massachusetts : Houghton Mifflin Company, 1989)
The field of learning disabilities continues to be a dynamic discipline, responsive to advance in education and changes in society. The fifth edition of learning disabilities: theories, diagnosis, and teaching strategies reflects these advance and changes.
1. Learning disabilities: A field in transition -- 2. Historical perspectives and emerging directions -- 3. Assessment -- 4. Clinical teaching -- 5. Systems for delivering educational services -- 6. Theoretical perspectives: Concepts and implications -- 7. Medical aspects of learning disabilities -- 8. At-risk preschool children -- 9. Learning-disabled adolescents and adults -- 10. Developmental and preacademic learning -- 11. Oral language: Listening and speaking -- 12. Reading -- 13. Written language: Written expression, spelling, and handwriting --14. Mathematics --15. Social and emotional behavior.
Includes bibliographical references and index.
Keywords: LEARNING DISABILITIES